2019
DOI: 10.1016/j.adro.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MRI Volumetric Changes After Hypofractionated Stereotactic Radiation Therapy for Benign Intracranial Neoplasms

Abstract: PurposeTo quantitatively assess volumetric changes after hypofractionated stereotactic radiation therapy (HFSRT) in patients treated for vestibular schwannomas and meningiomas.Methods and materialsWe retrospectively reviewed records of patients treated with HFSRT at our institution from 2002 to 2014. Patients received a median dose of 25 Gy in 5 fractions. After treatment, they underwent clinical and radiologic follow-up with magnetic resonance imaging (MRI) at 3- to 12-month intervals. Gross tumor volume was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Earlier studies of pseudoprogression, such as the report by Flickinger et al, demonstrate pseudoprogression rates of less than 2%, whereas more recent groups have reported rates up to 50%, though imaging varied among these studies. 16,24,25 Our definition of pseudoprogression, as a transient 3D volumetric increase, is more sensitive compared with pseudoprogression defined as planar growth in earlier studies and is closer to rates reported in more contemporary studies.…”
Section: Discussionmentioning
confidence: 53%
“…Earlier studies of pseudoprogression, such as the report by Flickinger et al, demonstrate pseudoprogression rates of less than 2%, whereas more recent groups have reported rates up to 50%, though imaging varied among these studies. 16,24,25 Our definition of pseudoprogression, as a transient 3D volumetric increase, is more sensitive compared with pseudoprogression defined as planar growth in earlier studies and is closer to rates reported in more contemporary studies.…”
Section: Discussionmentioning
confidence: 53%
“…While the radiological follow-up after a surgical tumor resection is unambiguous, interpretation of serial magnetic resonance imaging (MRI) following radiotherapy remains a matter of debate. Transient tumor enlargement, also called pseudoprogression, and loss of central contrast enhancement were described in 5–74% of patients in the first three years after SRS [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] . These well-known phenomena are of no or little relevance for the patient, since they are rarely symptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that transient tumor enlargement usually peaks at 6 months after SRS and resolves in 12–18 months [4] , [6] , [8] , [9] , [10] , [12] , [13] , [16] , [18] , [20] , [21] , [23] , [24] . But its resolution may require years for some patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several comparative studies suggested improved hearing and facial preservation rates along with better quality of life parameters with utilization of radiosurgery [62][63][64]. Nevertheless, response to radiosurgery in terms of tumor size may be variable particularly in the postintervention period as addressed in several studies [1,[65][66][67][68][69][70][71][72][73][74][75]. Transient volume changes during the postradiosurgical period have been referred to as transient expansion, tumor pseudoprogression, and transient tumor enlargement which may occur due to radiation induced swelling with several mechanisms.…”
Section: Changes After Radio Surgical Management Of Vsmentioning
confidence: 99%
“…The authors reported that transient expansion of VS frequently occurs at 6 to 18 months after radiosurgery whereas tumor growth seems to develop approximately at 3-4 years [72]. In a comprehensive analysis of MRI volumetric changes following HFSRT for benign intracranial neoplasms, Fega et al reported that transient volume expansion was a frequent finding after HFSRT of VS which was in association with temporary adverse effects [73]. The authors reported an overall 15% discordance rate regarding the neuroradiologist interpretation and volumetric MRI measurements, which underscores importance of incorporating volumetric measurements as part of detailed assessments to aid in decision making [73].…”
Section: Changes After Radio Surgical Management Of Vsmentioning
confidence: 99%